A Rationale for Non-Monotonic Group-Size Effect in Repeated Provision of Public Goods - Chengsi Wang; Galina Zudenkova (University of Mannheim, Department of Economics, 2014)
This paper analyzes the impact of a group-size change on contributing incentives in repeated provision of pure public goods. We develop a model in which the group members interact repeatedly and might be temporarily constrained to contribute to the public goods production. We show that an increase in the group size generates two opposite effects - the standard free-riding effect and the novel large-scale effect, which enhances cooperative incentives. Our results indicate that the former effect dominates in relatively large groups whilethe latter in relatively small groups. We provide therefore a rationale for nonmonotonic group-size effect which is consistent with the previous empirical and experimental findings.
urn:nbn:de:bsz:180-madoc-352598
Keywords: H40; D73; 330; pure public goods; repeated game; non-monotonic group-size effect